2021
DOI: 10.1101/2021.10.03.462599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine-mapping of nuclear compartments using ultra-deep Hi-C shows that active promoter and enhancer elements localize in the active A compartment even when adjacent sequences do not

Abstract: Megabase-scale intervals of active, gene-rich and inactive, gene-poor chromatin are known to segregate, forming the A and B compartments. Fine mapping of the contents of these A and B compartments has been hitherto impossible, owing to the extraordinary sequencing depths required to distinguish between the long-range contact patterns of individual loci, and to the computational complexity of the associated calculations. Here, we generate the largest published in situ Hi-C map to date, spanning 33 billion conta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Another approach is to brute-force genome-wide Hi-C or Micro-C; by performing 150 separate Hi-C experiments and sequencing deeper than ever before, a recent preprint by Gu et al reached 33 billion contacts 14 . However, such efforts 14 are not accessible to most labs and poorly compatible with perturbation experiments vital to uncovering mechanisms of organization. Instead, with RCMC we reach the local equivalent of 200 billion contacts with relatively modest sequencing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to brute-force genome-wide Hi-C or Micro-C; by performing 150 separate Hi-C experiments and sequencing deeper than ever before, a recent preprint by Gu et al reached 33 billion contacts 14 . However, such efforts 14 are not accessible to most labs and poorly compatible with perturbation experiments vital to uncovering mechanisms of organization. Instead, with RCMC we reach the local equivalent of 200 billion contacts with relatively modest sequencing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-mapping of nuclear compartments using ultra-deep Hi-C showed that active promoter and enhancer elements are localized in the active A compartment, whereas the flanking sequences are comprised entirely of inactive chromatin and are localized in the B compartment. These results suggest that the DNA-binding regulatory complexes undergo phase separation at the scale of individual DNA elements [16]. Phase separation also drives aberrant chromatin looping and cancer development [17].…”
Section: Linker Dna Length and Dna Sequencementioning
confidence: 93%
“…For example, a study (Sefer, 2021) found that H3K4me1, H3K9me3, and H3K27ac are some of the histone marks that are significantly predictive of most Hi–C interactions in human ES cells. Another study (Gu et al, 2021), using the ultra-resolution Hi-C contact map in lymphoblastoid cell lines (LCLs), observed the correlation of low H3K4me1 and H3K36me3 signals with the presence of discordant compartmentalization. Therefore, by modeling the relationship of histone modifications with the A/B compartments, CoRNN can capture the relevance of these marks in highlighting the properties of genomic compartmentalization.…”
Section: Resultsmentioning
confidence: 99%
“…This also means that it is difficult to predict the compartmental status of loci that have a mixture of both active and repressive chromatin marks, such as bivalent enhancers. Indeed, it is likely that these types of regulatory elements form unique chromatin interaction patterns (Gu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%